The Society of Cinema and Media Studies Annual Conference (2012) - Missy Molloy; Anthony Coman (Alphaville: Journal of Film and Screen Media, 2012)
Shortly after the hotel fire alarm interrupted Thursday’s hot midday panels, a disembodied voice assured everyone that there was no immediate danger and suggested that we all “return to our places”. This episode encapsulates the atmosphere of the Society of Cinema and Media Studies 2012 Boston conference, which unfolded over the course of five full days in late March. For any academic discipline, disorientation generates vitality, and whether it comes in the form of the shrill pitch and flashing lights of a false alarm, the sharp stab of a question from an established scholar, or the probing engagement of fellow panellists, the SCMS annual meeting is a destabilising force that draws strength from its members’ diverse interests, and typically sends its participants home feeling exhausted, yet invigorated.